Experimental and analytical investigation of fatigue crack propagation of T‐welded joints considering the effect of boundary condition. Issue 6 (3rd November 2016) - Sun, D; Gan, J; Wang, Z; Luo, P; Wu, W
Abstract: T‐welded joints are commonly employed in ship and ocean structures. The fatigue failure of structure components subjected to cyclic loading always occurs in T‐welded joints because of the metallurgical differences, tensile residual stress fields and stress concentrations. The former researches about T‐welded joints fatigue have in common that the boundary condition needs to be taken into account as an influencing parameter to predict the crack propagation during cyclic loading. In this paper, the crack growth behaviour in T‐welded joint processed with Q345D steel (Pingxiang Iron & Steel Co., Ltd, Hukou, Jiangxi Province in China) under the fatigue loading was analysed via analytical model and verified via experiment. The results show that the influence of boundary condition should be considered in T‐welded joint structure during crack propagation in weld toe area. The correction factor concerning the effect of boundary condition and modified Paris' equation was proposed according to the experimental results and verified by the following repeated experiments.